2019
DOI: 10.1186/s12974-019-1590-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miRNA signatures in CSF identifies upregulation of miR-21 and miR-146a/b in patients with multiple sclerosis and active lesions

Abstract: BackgroundMicroRNAs (miRNAs) have been reported as deregulated in active brain lesions derived from patients with multiple sclerosis (MS). In there, these post-transcriptional regulators may elicit very important effects but proper identification of miRNA candidates as potential biomarkers and/or therapeutic targets is scarcely available.ObjectiveThe aim of the study was to detect the presence of a set of candidate miRNAs in cell-free cerebrospinal fluid (CSF) and to determine their association with gadolinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…A gene with Pearson correlation coefficient > 0.5 and P < 0.05 was considered as a co-expression gene. A co-expression network was built for each gene related to prognosis and its co-expressed genes using Cytoscape software (version 3.7.1) [ 32 ]. GO function analysis and KEGG pathway analysis of these genes were also completed using DAVID [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…A gene with Pearson correlation coefficient > 0.5 and P < 0.05 was considered as a co-expression gene. A co-expression network was built for each gene related to prognosis and its co-expressed genes using Cytoscape software (version 3.7.1) [ 32 ]. GO function analysis and KEGG pathway analysis of these genes were also completed using DAVID [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the SYBR Green qPCR, the AllGlo qPCR method had a higher sensitivity and a wider linear range (10 3 -10 10 copies/μL), meaning that we could easily detect the miRNAs which were expressed in low abundance in the circulation. The levels of miRNAs in some body fluids such as urine, cerebrospinal fluid and exosome are much lower than those in serum or plasma, however studies had shown that they have great significance in the process of cancer development or some other diseases [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the SYBR Green qPCR, the AllGlo qPCR method had a higher sensitivity and a wider linear range (10 3 -10 10 copies/µL), meaning that we could easily detect the miRNAs which were expressed in low abundance in the circulation. The levels of miRNAs in some body fluids such as urine, cerebrospinal fluid and exosome are much lower than those in serum or plasma, however studies had shown that they have great significance in the process of cancer development or some other diseases [33,34,35].…”
Section: Discussionmentioning
confidence: 99%